Recruitment of Single-Stranded Recombinant Adeno-Associated Virus Vector Genomes and Intermolecular Recombination Are Responsible for Stable Transduction of Liver In Vivo - Nakai, Hiroyuki (American Society for Microbiology, 2000)
Recombinant adeno-associated virus (rAAV) vectors stably transduce hepatocytes in experimental animals. Following portal-vein administration of rAAV vectors in vivo, single-stranded (ss) rAAV genomes become double stranded (ds), circularized, and/or concatemerized concomitant with a slow rise and, eventually, steady-state levels of transgene expression. Over time, at least some of the stabilized genomes become integrated into mouse chromosomal DNA. The mechanism(s) of formation of stable ds rAAV genomes from input ss DNA molecules has not been delineated, although second-strand synthesis and genome amplification by a rolling-circle model has been proposed. To begin to delineate a mechanism, we produced rAAV vectors in the presence of bacterial PaeR7 or Dam methyltransferase or constructed rAAV vectors labeled with different restriction enzyme recognition sites and introduced them into mouse hepatocytes in vivo. A series of molecular analyses demonstrated that second-strand synthesis and rolling-circle replication did not appear to be the major processes involved in the formation of stable ds rAAV genomes. Rather, recruitment of complementary plus and minus ss genomes and subsequent random head-to-head, head-to-tail, and tail-to-tail intermolecular joining were primarily responsible for the formation of ds vector genomes. These findings contrast with the previously described mechanism(s) of transduction based on in vitro studies. Understanding the mechanistic process responsible for vector transduction may allow the development of new strategies for improving rAAV-mediated gene transfer in vivo.